How to get the most from what you read making inferences - Cotton, Eve; Maguire, Jim; The Center for Humanities (White Plains, N.Y. : The Center for Humanities)
Points out the confusion that results when one fails to understand the main idea in any medium, and emphasizes the importance of considering all the facts before making an assumption, using well-known literary works as practice tools.
Title from title screen
Keywords: Reading comprehension; Study skills; Books and reading